Self-Efficacy and Financial Literacy Influencing Employee Performance of West Sumatera Merchant Marine Polytechnic - Yuda Prabowo; Aimatul Yumna (Jurnal Manajemen Pelayanan Publik, 2023)
Employee performance is influenced by self-efficacy and financial literacy. The purpose of this study was to determine the effect of self-efficacy on employee performance, the effect of financial literacy on employee performance, and the effect of self-efficacy and financial literacy on employee performance at the West Sumatera Merchant Marine Polytechnic. This research is quantitative research with ex post facto methods. The population of this study was all employees at West Sumatera Merchant Marine Polytechnic. The research sample was selected by using a purposive sampling technique which only selected the civil servants totaling 73 people. The research instrument is a questionnaire. The data collection technique in this study was to distribute the questionnaire directly to the sample. The data analysis technique used multiple linear regression analysis with the help of SPSS statistics 25. The results showed that there is a positive effect of self-efficacy on employee performance, a positive effect of financial literacy on employee performance, and the effect of self-efficacy and financial literacy simultaneously on the employee performance of the West Sumatera Merchant Marine Polytechnic. So it is recommended that every employee and agency leader pay attention to self-efficacy and financial literacy factors to realize optimal employee performance.